PROSPECTIVE ACCOUNTING TEACHERS' VIEWS ON THE POST-COVID-19 LEARNING PROCESS AT SURAKARTA MUHAMMADIYAH UNIVERSITY: Pandangan Calon Guru Akuntansi Terhadap Proses Pembelajaran Pasca Covid-19 Di Universitas Muhammadiyah Surakarta - Agung Faizin; Harsono (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research was conducted to examine how prospective teachers view the post-Covid-19 learning process and how various variables (Optimization of Learning, Optimization of Student Participation) affect post-Covid-19 pandemic learning conducted with IT-based Teaching and Learning Activities. Partial least squares structural equation modeling (PLS-SEM) is the method used for data analysis in this study to analyze the data obtained after withdrawing data. This study involved Accounting Education students at Universitas Muhammadiyah Surakarta, vulnerable class of 2018-2022 where these students experienced the learning process during the pandemic and post-pandemic. Data were collected using a questionnaire distributed to students online. The results showed that based on the views of prospective teacher students that learning optimization factors, optimizing student participation can positively and significantly influence IT-based Teaching and Learning Activities at Universitas Muhammadiyah Surakarta after the Covid-19 pandemic.